n-Octanol oxidation on Au/TiO2 catalysts promoted with La and Ce oxides; Molecular Catalysis; Vol. 427 - Kotolevich Yu. I. Yuliya; Kolobova E. N. Ekaterina Nikolaevna; Khramov E. V. Evgeny Vladimirovich; Farias M. H. Mario; Zubavichus Ya. V. Yan Vitautasovich; Tiznado H.; Martinez-Gonzalez S.; Cortes Corberan V.; Mota-Morales Jo. D. Josue; Pestryakov A. N. Aleksey Nikolaevich; Bogdanchikova N. E. Nina Evgenjevna (2017, 2017)
Title screen